Good Editorial Practice: Editors as Educators - Marusic, Matko; Marusic, Ana (Journal of Nepal Health Research Council, 2009)
Not Uploaded, Key Words: Bibliometrics; Cross-Cultural comparison; Education; Professional; Retraining; Indexing; Journals; periodicals; Practice guidelines; Practice patterns; Publishing; Training support. DOI: 10.3126/jnhrc.v6i1.2434 Journal of Nepal Health Research Council Vol. 6, No. 1, Issue 12, April, 2008 Page: II-IX